MODEL PENDUGAAN DAYA SIMPAN BENIH KEDELAI [(Glycine max (L.) Merrill)] BIJI BESAR DENGAN PENGUSANGAN CEPAT SEBAGAI TEKNOLOGI PENENTU MUTU BENIH - Harun Rasyid (Jurnal Gamma, 2012)
MODEL PENDUGAAN DAYA SIMPAN BENIH KEDELAI [(Glycine max (L.)Merrill)] BIJI BESAR DENGAN PENGUSANGAN CEPAT SEBAGAI TEKNOLOGI PENENTU MUTU BENIHHarun RasyidStaf Pengajar Jurusan Agronomi, Fakultas Pertanian PeternakanUniversitas Muhammadiyah Malange-mail: rasyidharun30@yahoo.co.idABSTRACTFrom the results of the first study showed that b is closely seeds per hectare and harvest index are significant interaction between treatment and dose spacing of P fertilizer and harvesting of seed yield percentage variance analysis results are not significant interaction between treatment. Thick seed coat of the results of analysis of variance there was no significant interaction between treatments. The surface area of seeds and water absorption of soybean seeds are the result of analysis of variance significant interaction between spacing and fertilizer P. The content of phosphorus compounds shows that there is significant interaction between the treatment plant spacing and fertilizer P. The content of glucose and protein from the results of analysis of variance there is a significant interaction between treatment and dose spacing P fertilizer, while the fat content is not real interaction in treatment spacing and fertilizer P. spacing of 40 cm x 20 cm and P fertilizer dose of 100 kg / ha of SP-36 increase the harvest index, number of pods, seed weight per plant, seed weight per hectare, and the weight of seeds per hectare. Treatment plant spacing and fertilizer P effect on the physical form of the surface area of soybean seed and water absorption and nutrient content of glucose and soybean seed proteins. After empirically n phase I in the first stage of the research conducted to-2 in the second year. In the second year of this study, the size of the seed as genetic and environmental characteristics (spacing and fertilizer P) is suspected to be the cause of differences in the quality and storability of soybean seeds. Therefore, the models estimate the necessary seed storability of soybean seeds with a large pengusangan techniques quickly.Key word : germination power, fast pengusangan, seed storability of seed, and germination models.